Validating the component of E-learning antecedents, digital readiness and usage behavior towards E-learning performance: a pilot study - Jabar, Juhaini; Hasim, Mohamad Aidil; Sufian, Atirah; Ibrahim, Nor Fauziana (Society for Research and Knowledge Management, 2022)
With its plethora of benefits, E-learning has the potential to attract students to an educational environment. Unfortunately, E-learning can cause students to become passive learners. Most learning occurs asynchronously, and students typically feel estranged from their instructors and peers. This paper explains the pilot test approach to a proposed framework model based on E-learning antecedents, digital readiness, usage behavior and E-learning performance, before embarking on the extensive research necessary to develop best practices in E-learning. The content validity index and a pilot study were used to determine the usability and reliability of a survey questionnaire. Based on a simple random sampling plan, an online survey method was used to gather data from 102 respondents at the Universiti Teknikal Malaysia Melaka, Malaysia. The results indicate that the instrument's content validity index value is 0.97, which is significantly greater than the cut-off value of 0.8. The Cronbach alpha values for most of the constructs in the proposed framework model ranged between 0.905 and 0.970, indicating that the constructs are highly reliable. To contribute to the body of knowledge, the researchers provide an overview of the pilot test procedures as well as the methodology that was utilized. Based on the integration of the unified theory of acceptance and use of technology and task-technology fit models, a proposed framework model is presented to provide a more comprehensive framework model. It is concluded that the questionnaire items are adequate and acceptable for further investigation on a broader scale. Thus, the instrument can be examined further in other settings.